Beyond the four walls: The evolution of school psychological services during the COVID‐19 outbreak. Issue 7 (15th May 2021) - Schaffer, Gary E.; Power, Elizebeth M.; Fisk, Amy K.; Trolian, Teniell L.
Abstract: The emergence of the novel coronavirus disease (COVID‐19) in early 2020 led to the sudden temporary closure of K‐12 schools across the United States. Schools were tasked with providing remote instruction to students, and many of these children continued to require mental and behavioral health services provided by school psychologists. In this study, 675 school psychologists were surveyed across the United States to examine how their roles and responsibilities changed as a result of COVID‐19. Participants reported the perceived impact of COVID‐19 on students' mental health and difficulty serving students and families, as well as their concerns and recommendations pertaining to school reentry. Overall, respondents in this study reported that their roles and responsibilities notably changed because of COVID‐19. Participants noted their belief that children and educators will need increased mental health support upon returning to school. Implications for future practice and research are discussed.